LEGAL REGULATION OF EDUCATIONAL RELATIONS IN UKRAINE - Blikhar, Viacheslav; Babii, Serhii; Lieonov, Hlib (Socio-economic relations in the digital society, 2023)
Special attention to the issue of legal regulation of educational relations in society today paid. After all, the legal basis of such relations is laid in the Constitution of Ukraine and a large number of laws and other legal acts that regulate and regulate the conduct of the educational process in the state. The article develops an approach to the justification of educational law, which regulates and implements the right to education and receiving educational services guaranteed by the Constitution of Ukraine. In the course of the study, the need to distinguish educational relations into two blocks was substantiated: 1) directly educational, to which it is proposed to attribute the direct transfer of knowledge to the recipient of educational services; 2) relations related to educational ones. Among a number of such relations, attention is focused on labour, administrative, economic, family, financial, tax, budget relations, etc. The main characteristics of educational relations are singled out, namely: multilateralism, taking into account the variety of relationships that students of education have in the process of receiving educational services (this includes relations with the head of a higher education institution, scientific and pedagogical and pedagogical workers, parents and relatives, as well as legal entities that can pay for education); subject-centrism of a higher education seeker who has the right and undertakes to obtain an education; individuality and inalienability of the process of obtaining education since the right to education cannot be delegated to another subject; functional variety and multi-stage implementation. This study can become a basis for improving the normative and legal field of regulation of the educational sector.